Systematic Literature Review: Analysis of Early Childhood Education Teachers' Resilience Capabilities in Facing Professional and Contextual Challenges - Faizin, Imam; Sarwi, Sarwi; Sudarmin, Sudarmin; Cahyono, Adi Nur (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to analyze the resilience capabilities of Early Childhood Education (ECE) teachers in facing professional and contextual challenges through a Systematic Literature Review (SLR) approach. Using the PRISMA method, 12 articles from 2015–2024 were identified and analyzed to explore the internal and external factors of ECE teachers' resilience. The analysis results indicate that 33% of the articles highlight the role of internal resilience factors such as self-compassion, ego-resilience, and self-esteem. In comparison, 50% of the articles emphasize the importance of social support, institutional policies, and training as external resilience factors. 17% of the articles discuss the interaction between internal and external factors. These findings affirm that resilience results from a dynamic interaction between the individual and their environment. This research recommends developing resilience-based training programs and institutional policies that support the well-being of ECE teachers. With a holistic approach, early childhood education teachers are expected to be better prepared to face professional and contextual challenges that optimally contribute to supporting the development of young children.